Background factors of crisis distance learning perception - O. A. Valger; I. A. Vezner; O. A. Sklyomina (Образование и наука)
Introduction. Crisis distance learning was an emergency response of higher education systems to the COVID-19 pandemic, and its elements still remain active in world universities. Literature review demonstrates that improvement of quality of offered courses does not demonstrate a stable correlation with improvement of students’ feedback.Aim. This study aims to explore the influence of background factors on students’ perception of this format of education and identify and analyse the factors that predetermine the polarisation of students’ satisfaction levels as extremely high or extremely low.Methodology and research methods. The research frame combined qualitative and quantitative methods and included a series of semi-structured interviews with volunteers from the student which then served as a basis for an in-depth questionnaire with the sample of 115 respondents in the general population sample of 558 students. The Likert scale and qualitative content-analysis were employed to assess the level of satisfaction with the period under study and to build the tree of concepts perceived as its advantages and disadvantages. To identify the major factors that influenced the student perception, the multiple-choice questions that addressed the students’ background conditions were weighed in comparison with the satisfaction level response in the general sample with the application of one-way analysis of variance (the Kruskal-Wallis criterion).Results. The results show that there is polarisation in the student body. While the majority adapted to crisis distance education, there are two distinct minorities who consider it successful or unbearable. The background factors that influence the student perception significantly are the year of their programme, their commute patterns, their living conditions, and their employment status.Scientific novelty. Overall perception of crisis distance learning by bachelor students reflects the struggles that the students face outside the classroom and distinct groups of students have their reactions determined by these factors to a degree where improvement of teaching methods cannot assist. The distribution of satisfaction levels in the sample proves that crisis distance learning highlights economic inequality.Practical significance. Administering higher education in this pandemic and the following pandemics to come should include a complex of measures aimed at compensating the background factors that predetermine students’ low satisfaction levels in crisis distance education.